RESOURCE-BASED STRATEGIC MANAGEMENT IN DIGITAL MARKETPLACES: CHALLENGES AND E-COMMERCE STRATEGIES OF INDONESIAN MSMES - Halek Mu'min; Sachin Vedpathak (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study investigates the challenges and strategic management approaches of digital Micro, Small, and Medium Enterprises (MSMEs) operating in Indonesia's e-commerce ecosystem through the theoretical lens of the Resource-Based View (RBV). Employing a qualitative multiple case study methodology, we examine how internal resource configurations influence competitive positioning and strategic efficacy. Our findings reveal that while MSMEs effectively leverage indigenous market knowledge and entrepreneurial flexibility, significant deficiencies in financial capital, advanced digital competencies, and technological infrastructure impede their ability to develop valuable, rare, inimitable, and non-substitutable (VRIN) resources critical for sustained competitive advantage. Strategic responses are predominantly characterized by reactive resource allocation, organic capability building, and incremental technology adoption. The study identifies a clear mediating relationship between resource endowments and strategic effectiveness, demonstrating that performance outcomes are strongly contingent upon the alignment between internal capabilities and e-commerce strategies. This research contributes to RBV theory by illuminating its application in digitally transforming emerging economies and provides empirical insights to inform policy interventions and managerial practice in the Indonesian digital MSME sector.